The decline of walleye populations: an ecological tipping point? - Greg G. Sass (FACETS)
Walleye/ogaa (Sander vitreus (Mitchill)) (hereafter, walleye; ogaa = Ojibwe translation) populations have historically supported important multi-use, harvest-oriented fisheries. Despite intensive management, walleye populations have declined in the midwestern United States raising concerns about the sustainability of the species. Numerous factors have been implicated in walleye population declines, including climate change, habitat loss, invasive species, species-interactions, production overharvest (i.e., harvest consistently exceeding annual production), and changing angler behaviors. These factors have negatively influenced natural recruitment and contributed to depensatory recruitment dynamics. I provide a review and perspective suggesting that the current trajectory of walleye populations is at or nearing an ecological tipping point. Although fish populations are often considered compensatory (i.e., negatively density-dependent), current walleye populations appear prone to depensation (i.e., positive density dependence). My review and perspective suggest that a compensatory management perspective for walleye is misaligned. A change in management towards a depensatory resource focus using ecosystem-based fisheries management and the recognition of walleye fisheries as social–ecological systems is needed for conservation. If compensatory management ensues, walleye persistence will likely be further threatened because many drivers of change are outside of managerial control, and those commonly used within managerial control have seemingly been ineffective for sustaining or rehabilitating naturally reproducing walleye populations.